Taxonomic revisión of Microstelma (Apocynaceae, Asclepiadoideae, Asclepiadeae, Gonolobinae), endemic to Mexico, with two new species - Alvarado-Cárdenas, Leonardo O. (Instituto de Ecología, A.C., 2024)
Background and Aims: The subtribe Gonolobinae is one of the most diverse in the family Apocynaceae and its taxonomic history continues to undergo numerous changes. Matelea is one of the genera within the subtribe that has undergone the most changes and numerous taxa have been segregated, including the monotypic Microstelma. This paper aims to present an updated treatment of Microstelma and the description of two new species, as well as an identification key, images and descriptions of its species. Methods: Field trips were made and herbarium specimens including types were observed. Taxonomic literature on the taxa treated was consulted, a revision of the genus was made, species plates and distribution maps were prepared, and their conservation status was evaluated. Key results: Three species are recognized for Microstelma, all endemic to Mexico, two named as new species: M. jimenezii (Michoacán) and M. tenorioi (Guerrero and Oaxaca). The length of the pedicels, the morphology and the reticulation pattern of the corolla, as well as the morphology of the gynostegium and its distribution, allowed to recognize the species. Conclusions: Microstelma now has three species and is, together with Thoreauea, one of the most diverse endemic genera of Apocynaceae of Mexico. It is important to continue with the revision work for a better understanding of the morphology and systematics of these groups.